Organizational Citizenship Behavior (OCB) Through Strengthening Learning Organization, Servant Leadership, Personality, dan Job Satisfaction in Indonesian Islamic Elementary School - Dewi Indah Susanti; Didik Notosudjono; Herfina Herfina (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the direct and indirect effects of Learning Organization, Servant Leadership, Personality, and Job Satisfaction on teachers' Organizational Citizenship Behavior in Indonesian Islamic Integrated Elementary Schools. A quantitative cross sectional survey design was employed involving 176 permanent teachers selected through proportional random sampling from Islamic Integrated Elementary Schools in East Jakarta, Indonesia. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares. The findings reveal that Personality has a positive and significant effect on Organizational Citizenship Behavior and Job Satisfaction. Job Satisfaction also significantly enhances Organizational Citizenship Behavior, indicating its important role in fostering teachers' discretionary and voluntary contributions beyond formal responsibilities. Learning Organization significantly improves Job Satisfaction and indirectly strengthens Organizational Citizenship Behavior through Job Satisfaction. In contrast, Servant Leadership does not exhibit significant direct or indirect effects within the proposed structural model. The mediation analysis confirms that Job Satisfaction functions as a critical psychological mechanism linking organizational and individual resources to Organizational Citizenship Behavior. These findings highlight the importance of strengthening organizational learning practices, cultivating positive teacher personality characteristics, and improving job satisfaction to promote sustainable organizational effectiveness and educational quality in Indonesian Islamic elementary schools.